Fatigue Behavior of Cold-Worked High-Interstitial Steels - Sedat Güler; Alfons Fischer (Metals, 2018)
The austenitic high-nitrogen (AHNS) and high-interstitial steels (AHIS) with more than 0.6 weight-% N allow for a yield strength above 1.1 GPa and a tensile strength above 1.5 GPa by maintaining an elongation to fracture markedly above 30%. These steels gain their prominent mechanical properties from the fact that at the chosen sum of C+N and C/N-ratios, the concentration of free electrons is higher compared to that of other steels. Thus, the capacity to dissipate plastic work under monotonic tensile loading is unique. Now, the fatigue limit of austenitic steels in general is mainly governed by the sum of interstitials and should be further improved by cold working. Unfortunately, this is not the case for the AHNS and AHIS and is in contrast to the classical CrNiC- or CrMnC-steels. Thus, tensile and fatigue tests of cold-worked samples were conducted and analyzed by scanning- and transmission-electron microscopy. This paper tries to elucidate the metallurgical reasons, as well as the material engineering aspects, of such peculiar behavior of AHNS and AHIS.